Eosinophilic Esophagitis: Atopy Conditions of the Esophagus - Puspa Zuleika (HM Publisher, 2021)
Eosinophilic esophagitis is an immune-allergic pathology of multifactorial etiology(genetic and environmental) characterized by major symptoms of esophagealdysphagia and eosinophil-predominant inflammation of the esophageal mucosathat affects both pediatric and adult patients. EoE is an immune-mediated diseaseby which environmental and food antigens stimulate the Th2 inflammatorycascade. It is correlated with food allergy and atopy condition such as asthma, atopydermatitis, rhinitis allergic and often in conjunction with Gastroesophageal RefluxDisease (GERD). Eosinophilic esophagitis (EoE) was first described in the 1990s,showing an increasing incidence and prevalence since then, in the United States isestimated to be approximately 57 per 100,000 persons being the leading cause offood impaction and the major cause of dysphagia. Its symptoms, which includeheartburn, regurgitation, and esophageal stenosis. This symptomps similar to thoseof gastroesophageal reflux disease, causing delays in diagnosis and treatment. Theendoscopic findings such as furrows, esophageal mucosa trachealization, andwhitish exudates, this diagnosis should be confirmed histologically confirmed bybiopsy on the presence of more than 15 eosinophils per high-power field and theexclusion of other causes of eosinophilia. Management includes medications, diet,and surgical dilatation.